Additive Effect of Dornase Alfa and Nacystelyn on Transportability and Viscoelasticity of Cystic Fibrosis Sputum - Feng Sun; Shusheng Tai; Thomas Lim; Ulrich Baumann; Malcolm King (Canadian Respiratory Journal)
OBJECTIVE: To investigate the effect of dornase alfa (DA), Nacystelyn (NAL) and their combination on mucociliary transportability and mucus viscoelasticity of cystic fibrosis (CF) sputum, and to assess whether the combination possesses an additive effect.